Study On Nematocysts Of Scleractinia Coral, Stylophora subseriata From Coral Reef Area In The Coast Of Bulutui, North Minahasa - Kamuntuan, Reffando Alfaro Fabio Fabien; Paruntu, Carolus Paulus; Roeroe, Kakaskasen Andreas; Lintang, Rosita Anggreiny J; Manembu, Indri Shelovita; Schaduw, Joshian Nicolas William (Jurnal Ilmiah Platax, 2024)
This study aims to identify the type, size dimension, and composition of nematocysts from the Scleractinia coral, Stylophora subseriata. This study was carried out from March to May 2023. Observations and measurements of nematocyst cells were conducted using an Optika 4083 B3 microscope connected to a computer equipped with Optika View 7 software. S. subseriata has three main types of nematocyst, i.e., type I micro basic p-mastigophore (MpM- I), type II micro basic p-mastigophore (MpM-II) and micro basic b-mastigophore (MbM).  Type MpM-I has an average capsule length of 182.10 µm, capsule width of 38.98 µm, and shaft length of 76.45 µm;  MpM-II has an average capsule length of 166.72 µm, capsule width of 41.60 µm, and shaft length of 108.48 µm; and MbM has an average capsule length of 154.84 µm and capsule width of 30.96 µm. The nematocysts composition consists of MpM-I 26.67 %, MpM-II 23.33 %, and MbM 50.00 %.  The MbM type is nematocyst dominant in this coral species.  Future study is recommended to examine the comparative characteristics of nematocysts from S. subseriata with other species of corals in the same genus to determine the specific nematocyst of each type of coral with the role of their particular types of nematocyst. Keywords: Bulutui coast, nematocyst, North Minahasa, Scleractinia, Stylophora subseriata Abstrak Penelitian ini bertujuan untuk mengidentifikasi tipe, dimensi ukuran dan komposisi nematosit dari karang Scleractinia, Stylophora subseriata. Studi ini dilakukan dari Maret - Mei 2023. Pengamatan dan pengukuran sel nematosit dilakukan menggunakan mikroskop Optika 4083 B3 yang terhubung dengan komputer yang dilengkapi software Optika View 7. S. subseriata memiliki tiga tipe nematosit utama, yaitu microbasic p-mastigophore tipe I (MpM-I), microbasic p-mastigophore tipe II (MpM-II) dan microbasic b-mastigopore (MbM).  Tipe MpM-I memiliki rata-rata panjang kapsul 182,10 µm, lebar kapsul 38,98 µm, dan panjang tangkai 76,45 µm;  MpM-II memiliki rata-rata panjang kapsul 166,72 µm, lebar kapsul 41,60 µm, dan panjang tangkai 108,48 µm; serta MbM dengan panjang kapsul 154,84 µm dan lebar kapsul 30,96 µm. Komposisi nematositnya terdiri dari MpM-I 26,67 %, MpM-II 23,33 % dan MbM 50.00 %.  Tipe MbM adalah nematosit yang dominan dalam spesies ini.  Penelitian selanjutnya disarankan untuk meneliti perbandingan antara karakteristik nematosit dari S. subseriata dengan jenis karang lainnya dalam satu genus untuk mengetahui nematosit spesifik dari masing-masing jenis karang tersebut sehubungan dengan peran dari tipe-tipe nematosit spesifiknya.       Kata kunci: Minahasa Utara, nematosit, Pesisir Bulutui, Scleractinia, Stylophora subseriata